DjunkGo: A Mobile Application for Trash Classification with VGG16 Algorithm - Wulandari, Sekar Ayu; Ma’ruf, Muhammad; Priyatno, Aditya Rachman; Halimun, Naomi; Abdulah, Zeni Malik; Amartiwi, Utih (GMPI Conference Series, 2023)
Garbage is one of the big problems in many countries including Indonesia. A bad waste management and low awareness of people participating in sorting the trash are 2 obstacles that we face in daily life. However, if we can ask them to sort the trash properly, they will not only help the waste collector, but also improve the waste management in the country. That encourages us to develop a mobile application that helps people to identify the type of the trash they have so that they can sort it by themselves. This application applies image processing and VGG16 algorithm to identify the trash with accuracy 90%. Furthermore, this application also links them to an appropriate agency that can recycle their trash based on its type. Therefore, the waste sorting process will be easier and recycling is also faster.